Construction claims & responses : effective writing & presentation - Hewitt, Andy (writer on construction claims) (Chichester, West Sussex, UK : John Wiley & Sons Inc, 2016)
' A practical, step-by-step guide for contracts managers, commercial managers, project managers, quantity surveyors, engineers and architects on the preparation of and responses to construction claims. Everyone involved in the preparation or review of construction claims should have this book to hand. The book examines the different types of claim common to construction contracts and presents a step-by-step guide to demonstrate the process of building up the submission of a claim and covers: Various types of claim. How the claim may be split into sections dealing with the details of the contract, the cause, the effect, entitlement and quantum. What this section is attempting to demonstrate or achieve and why. What should be included within the section and why. Worked examples of typical claims and responses with sample wording.'--
Introduction -- Contract administration for claims -- Types of claim -- Presentation -- The essential elements of a successful claim -- The preliminaries to the claim -- The extension-of-time claim -- The claim for additional payment -- The appendices and editing -- Claim responses and determinations -- A note on dispute boards.
Includes index.
Description based on print version record and CIP data provided by publisher.
Keywords: FIDIC forms of contract; Construction contracts; Claims; LAW / Construction; Electronic books